2000
DOI: 10.1128/aac.44.10.2845-2847.2000
|View full text |Cite
|
Sign up to set email alerts
|

The d -Alanine Residues of Staphylococcus aureus Teichoic Acids Alter the Susceptibility to Vancomycin and the Activity of Autolytic Enzymes

Abstract: Recently, Staphylococcus aureus strains with intermediate resistance to vancomycin, the antibiotic of last resort, have been described. Multiple changes in peptidoglycan turnover and structure contribute to the resistance phenotype. Here, we describe that structural changes of teichoic acids in the cell envelope have a considerable influence on the susceptibility to vancomycin and other glycopeptides. S. aureus cells lacking D-alanine esters in teichoic acids exhibited an at least threefold-increased sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
174
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(187 citation statements)
references
References 21 publications
(22 reference statements)
6
174
0
Order By: Relevance
“…For instance, the intermediate vancomycin-resistance phenotype in S. aureus is due to an increased amount of non-amidated glutamine residues in the peptidoglycan. It has been suggested that the increased resistance in these strains is due to the "affinity trapping" of vancomycin in the thickened cell wall [17,18].…”
Section: Cell Permeabilitymentioning
confidence: 99%
“…For instance, the intermediate vancomycin-resistance phenotype in S. aureus is due to an increased amount of non-amidated glutamine residues in the peptidoglycan. It has been suggested that the increased resistance in these strains is due to the "affinity trapping" of vancomycin in the thickened cell wall [17,18].…”
Section: Cell Permeabilitymentioning
confidence: 99%
“…A reduced degree of teichoic acid D-alanine substitution leads to reduced autolytic activity and, concomitantly, the methicillin MIC rises (O'Brien et al, 1995). The reduction of D-alanine esterification of teichoic acids has a negative effect on vancomycin tolerance, on the other hand (Peschel et al, 2000), which may be an indication to the observed 'incompatibility' of vancomycin and methicillin resistance in some in vitro generated mutants (Brandenberger et al, 2000;Sieradzki & Tomasz, 1997).…”
Section: Influence Of Autolytic Activitymentioning
confidence: 99%
“…Tolerance mechanisms remain elusive to this day, even if recent works on Streptococcus pneumoniae and S. aureus have suggested the involvement of impaired autolysin regulation systems (3,18) or modifications in the cell wall composition (7,17). Studies should be undertaken to explore the mechanism of the phenomenon of S. lugdunensis tolerance to glycopeptides observed in the present work and to evaluate its clinical implications.…”
mentioning
confidence: 99%